JOURNAL OF GOVERNMENT & POLITICS : The Growth of E-Government in the Government of Yogyakarta City - Danang Sri Wibowo , Irwan Abdullah (FISIPOL UMY, 2014)
The implementation of -government is, actually, not a new issue in the government .